A Rhetoric of Aesthetic Power - Kock, Christian. author. aut Link
X, 386 p. 41 illus., 2 illus. in color.
Keywords: This book offers a theory of those formal properties of art that are apt to afford strong aesthetic experience – a project resembling Aristotle’s in the Poetics, where he analysed structures in tragedies that condition the “peculiar pleasure” of tragedy. However, the book’s scope cuts across all genres of literature and also includes classical music – the formal art par excellence. Drawing on a wide array of recent theoretical work and empirical evidence, the book closely analyses dozens of examples of both art forms. Besides Aristotle, major inspiration comes from two modern master thinkers: the linguist Roman Jakobson, who defined the “poetic function” of language, and the rhetorician Kenneth Burke, who proposed a “psychological” concept of form. Throughout, the book argues for aesthetic experience as an end in itself and a component of quality of life, one to which everyone should have access – rather than just a means to other ends. Christian Kock is Emeritus Professor at the University of Copenhagen. Formerly an Associate Professor of English Literature and a Visiting Professor at Indiana University, he was Professor of Rhetoric from 1997 to 2018. He still publishes extensively, mainly on argumentation and political debate, as well as on the aesthetics of literature and classical music. .